A Analysis of Islamic Economic Transformation in Indonesia: A Case Study of Economic Policy Implementation in the Banking Sector: Analisis Transformasi Ekonomi Syariah di Indonesia: Studi Kasus Penerapan Kebijakan Ekonomi di Sektor Perbankan Syariah - Nawewi; s, Nawewi (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2024)
The rapid development of the Islamic economy, especially in the Islamic banking sector in Indonesia, raises the need for in-depth evaluation of policies and their impact on economic transformation. This research aims to analyze the implementation of Islamic economic policies and their impact on Islamic economic transformation in Indonesia. Using a qualitative approach with a literature study method, this research examines academic sources and policy documents to understand the role of fintech, Islamic insurance, and the social sector in the development of the Islamic economy. The findings show that fintech plays a crucial role in improving financial inclusion, Islamic insurance contributes to liquidity and growth, and optimization of the social sector supports sustainable development. The implications of this study suggest the need for continued policy support and collaboration between the government, financial institutions, and society to strengthen the Islamic economic sector and address regional and global challenges